PERSEPSI MASYARAKAT TERHADAP PELAYANAN DI PUSKESMAS MUARA SAHUNG - Afianti, Maya (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research was conducted to 1) analyze the implementation of Kaur Muara Sahun District Health Center services and 2) analyze public perceptions of Kaur Muara Sahun District Health Center services. The type of research used in this research is qualitative research. This research uses a descriptive method, which is carried out based on the approach, content and depth of the research topic. The data in this research was obtained from primary and secondary data. Data collection methods include observation methods, interview methods, and documentary methods. Data analysis techniques use data reduction, data visualization, and decision making/validation. The results of this research are as follows. One). The public's perception of health services at the Muara Sahung Community Health Center, Kaur District, is very positive and responsive. This is assessed based on factors that influence public perception according to Robbins, 2002 which states that there are three factors that influence public perception. This includes: a). The recognizing party (recogniser), b). An object or object, c). The context in which the observation is made. 2). The Puskesmas employees have also worked hard to continue to increase public awareness of health services at the Muara Sahung Puskesmas, Kaur District.